Characteristics of Patients with Obstetric and Gynecologic Fistula in Jakarta - Djusad, Suskhan; Sonia, Ambalagen; Natanael, Anthonyus (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To know the characteristics of patients with obstetrics and gynecologic fistula in Dr. Cipto Mangunkusumo Hospital, Jakarta. Method: This study was a descriptive design using secondary data from medical records and patient database during 2011-2016. Result: There were 68 subjects with fistula. From 2011-2016, there were 5 cases (7.4%), 19 cases (27.9%), 16 cases (23.5%), 11 cases (16.2%), 8 cases (11.8%), and 9 cases (13.2%) of fistula; respectively. The average age of subjects was 38 years old and only 34 subjects have complete data. Gynecologic and obstetric fistula were 17 cases each. As total 28% of fistula cases were vesicovagina fistula, 12% were rectovaginal fistula, 9% were anovagina fistula, and the other types of fistula were 2%. Among 34 subjects, there were 21% of vesicovagina fistula and 3% of rectovagina fistula, which were caused by iatrogenic. There were 7% of vesicovagina and rectovagina fistula each and 9% of anovagina fistula were caused by obstetric problems. The iatrogenic procedures found from this study were total abdominal hysterectomy (16%), vaginal hysterectomy (3%), and neovagina (3%). Conclusion: The trend of cases is decreasing during the present years (2011-2016). Gynecologic fistula cases caused by iatrogenic are the major problems, but the obstetrics fistula cases decreasing following the labor monitoring is much better nowadays. [Indones J Obstet Gynecol 2016; 4-4: 212-217] Keywords: gynecologic fistula, iatrogenic, obstetric fistula